The Jesuit Order as a Synagogue of Jews : Jesuits of Jewish Ancestry and Purity-of-Blood Laws in the Early Society of Jesus - Maryks, Robert Aleksander; Gow, Andrew Colin; Gow, Andrew Colin (Brill, 2009)
In The Jesuit Order as a Synagogue of Jews the author explains how Christians with Jewish ancestry went within less than forty years from having a leading role in the foundation and development of the Society of Jesus to being prohibited from membership in it.
Knowledge Unlatched
English
Keywords: Humanities; History; General